Emergency care for palliative patients in the emergency room: A literature review - Ni Luh Putu Inca Buntari Agustini; Ni Luh Dwi Indrayani; I Nyoman Widiadnyana; Ni Luh Putu Yudi Aprianini; Putu Indah Jelita Lestari; Ni Ketut Erawati; I Made Jaya Kusuma; Vinda Ekabudiningsih (Malahayati International Journal of Nursing and Health Science, 2025)
Background: A lot of research has been done on the treatment of palliative patients who come to the emergency department. Although there are several models, it is still difficult to integrate palliative care into the ED. Purpose: To determine how emergency care for palliative patients is implemented in the emergency department.   Method: The PCC framework (Population: palliative patients, Concept: emergency care, Context: emergency department) was used to generate the article questions for this literature review. A search for articles was conducted during November and December, 2024. Pubmed, the ScientDirect database and other resources were used as data sources. “Palliative care" OR "palliative medicine" OR "hospice and palliative care nursing" AND "emergency treatment" OR "emergency medical services" AND "emergency room" OR "ER" were used as keywords. Results: Emergency care for palliative patients in emergency room has been implemented with a focus on symptom management and reducing the patient's suffering, maintaining patient comfort and involving families in decision making, with effective communication being essential. However, there are still serious barriers and challenges such as lack of staff education, problems with current emergency department systems and processes. Conclusion: The knowledge and skills of nurses and other health workers need to be improved and more in-depth studies need to be carried out so the implementation of palliative patient care in emergency cases can be optimized.